Legal labeling of halal products using the official names of haram products (A case study of halal certification for tuak, beer, and wine products) - Firdaus, Muh Nur Ridho Chaerul; Dahlan, Muh Nur Fithri; Elizatun, Elizatun; Muhris, Ahmad (Journal of Halal Science and Research, 2025)
With Muslims comprising 91% of its populace, Indonesia is home to the world's largest Islamic community. This demographic landscape makes the integrity of halal certification essential for the nation's ambition to become a leading global hub for the halal industry. Consequently, this study offers a critical analysis of the practice of using nomenclature associated with forbidden (haram) items on the labels of halal-certified products. It was found that products containing the names ‘tuak’, ‘beer’, and ‘wine’ received halal certification. According to BPJPH, this issue is only a difference of opinion regarding the naming of the product, while the halal content has been guaranteed. However, in muamalah, the measure is the object of naming, not the name. This study aims to determine the legal status of the use of these names on halal products in Islam. The method used in this research is a descriptive analysis method with the Maqashid Sharia approach. The result of this study is that the legal status of using halal product names for products with names containing those names in Islam is not allowed. The results of this study can serve as a recommendation for the government to establish clear regulations regarding product naming in order to create legal certainty in this matter and prevent similar debates in the future. Keywords: BPJPH MUI conflict, Halal certification Indonesia, Halal product naming, Indonesia halal economy, Maqashid syariah halal.